2011
DOI: 10.1002/chem.201102251
|View full text |Cite
|
Sign up to set email alerts
|

General Au‐Catalyzed Benzannulation Towards Naturally Occurring Carbazole Alkaloids from Methoxypropadiene

Abstract: Accessible alkaloids: Naturally occurring carbazole alkaloids, such as clauszoline‐K, ‐L, ‐M, and ‐N, 3‐formyl‐7‐hydroxycarbazole, and siamenol, were synthesized through a gold‐catalyzed cyclization reaction of 1‐(indol‐2‐yl)‐2‐methoxy‐2,3‐allenols, which are readily available from indolecarbaldehydes and methoxypropadiene (see scheme; R1=Me, carboxylic acid/ester, or aldehyde; R2=prenyl or H; R3=H or Me). The reaction demonstrates atom economy, high selectivity, and high yields, mostly with catalytic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…[141] With regard to indole alkaloids, in 2011 Ma and co-workers reported the gold(I)-chloride-catalyzed carbocyclization of 2,3-allenols 123 to carbazoles 124 as key step in the total synthesis of siamenol and clauszoline K,L or clausine M derivatives (Scheme 50). [142] Scheme 50. Gold-catalyzed carbocyclization of 123 as key step in the synthesis of siamenol and clauszoline K,L or clausine M derivatives.…”
Section: Application Of Gold Catalysis To the Synthesis Of Indole-basmentioning
confidence: 99%
“…[141] With regard to indole alkaloids, in 2011 Ma and co-workers reported the gold(I)-chloride-catalyzed carbocyclization of 2,3-allenols 123 to carbazoles 124 as key step in the total synthesis of siamenol and clauszoline K,L or clausine M derivatives (Scheme 50). [142] Scheme 50. Gold-catalyzed carbocyclization of 123 as key step in the synthesis of siamenol and clauszoline K,L or clausine M derivatives.…”
Section: Application Of Gold Catalysis To the Synthesis Of Indole-basmentioning
confidence: 99%
“…For the purpose of synthesizing the naturally occurring carbazole, a methoxy group has been introduced to the 2‐position of the starting 1‐(indol‐2‐yl)‐2,3‐allenols. We observed that AuCl is a much more effective catalyst than PtCl 2 . In the total synthesis of siamenol, we utilized this transformation as the key step for constructing the carbazole skeleton from the required methoxy‐substituted allenol 1 a .…”
Section: Reaction Developmentmentioning
confidence: 99%
“…The reaction occurred smoothly at room temperature to afford a series of poly‐substituted carbazoles. Two years later, our further investigation led to the observation of AuCl as a much more effective catalyst for this transformation . Due to the easy availability of the starting materials, this simple and mild Au‐catalyzed reaction of 1‐(indol‐2‐yl)‐2,3‐allenols provides a general route to differently substituted carbazoles.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] In particular, a gold-catalyzed hydroarylation of N-allenylmethylindoles that furnishes dihydro-pyrido[1,2-a]-1H-indoles has been described (Scheme 1a). 37 Moreover, several cyclizations of 1-(indol-2-yl)-allenols (functionalized 2-allenylmethylindoles) that afford carbazoles have been developed using different metals such as Au, [38][39][40] Pt [41][42][43] or Pd 44 (Scheme 1b).…”
Section: Figure 1 Naturally Occurring 49-dihydro-1h-carbazolesmentioning
confidence: 99%